2009
DOI: 10.4049/jimmunol.0802124
|View full text |Cite
|
Sign up to set email alerts
|

Aire-Deficient C57BL/6 Mice Mimicking the Common Human 13-Base Pair Deletion Mutation Present with Only a Mild Autoimmune Phenotype

Abstract: Autoimmune regulator (AIRE) is an important transcription regulator that mediates a role in central tolerance via promoting the “promiscuous” expression of tissue-specific Ags in the thymus. Although several mouse models of Aire deficiency have been described, none has analyzed the phenotype induced by a mutation that emulates the common 13-bp deletion in human APECED (autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy) by disrupting the first plant homeodomain in exon 8. Aire-deficient mice with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
146
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 121 publications
(160 citation statements)
references
References 70 publications
11
146
3
Order By: Relevance
“…This does not indicate that the naive T-cell repertoires are identical in wt and Aire-deficient mice, as the development of autoimmunity suggests the presence of self-reactive clones in the latter. Four Aire-deficient mouse models have been reported [3,14,16,34,35]. The similar phenotype shared by these models is less severe than that of APECED patients [16,[35][36][37].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This does not indicate that the naive T-cell repertoires are identical in wt and Aire-deficient mice, as the development of autoimmunity suggests the presence of self-reactive clones in the latter. Four Aire-deficient mouse models have been reported [3,14,16,34,35]. The similar phenotype shared by these models is less severe than that of APECED patients [16,[35][36][37].…”
Section: Discussionmentioning
confidence: 95%
“…An early study [15] comparing the features of TCRb repertoires between wt and Aire-deficient mice found differences in the immunoscopes of three of the 24 Vb families, suggesting that Aire may significantly perturb the repertoire. A more recent study [16] of the Vb gene usage and CDR3b lengths of naive CD4…”
Section: Cd8mentioning
confidence: 99%
“…We embarked on a study of the influence of AIRE on the in vitro and in vivo suppressor activity of CD8 + CD28 low Treg. Mice carrying a 13-bp mutation in the AIRE gene that disrupts the PHD1 domain in exon 8 were previously discussed (21). It was demonstrated that these mice developed mild symptoms of autoimmune pathology, similar to other AIRE-deficient mice on the C57BL/6 background.…”
Section: Quantitatively Unaltered Development Of Transcriptionally Andmentioning
confidence: 99%
“…In AIRE°mice, marginally reduced numbers of CD4 + Foxp3 + Treg may develop. However, molecular analysis of the TCR repertoire of WT and AIRE°CD4 + Foxp3 + Treg failed to detect any difference, and these cells have unaltered in vitro and in vivo suppressive activity (20,21,30,32,33). In APECED patients, decreased expression of Foxp3 and impaired suppressive function of Treg were observed (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation